P327 Symptom relevance attributed by inflammatory bowel disease patients has a differential impact on their quality of life. (16th January 2018) - Casellas, F; Herrera de Guise, C; Robles, V; Navarro, E; Guirola, M; Borruel, N
Abstract: Background: The role of inflammatory bowel disease (IBD) symptoms and their importance in the management of IBD is well known. However, the relevance that IBD patients assign to each symptom and its potential effect on patients' perception of health has been less well studied. The aim of this study was to establish whether the relevance attributed by patients to different symptoms is related to their overall quality of life (QoL). Methods: A prospective, observational, anonymous study was conducted in consecutive IBD patients with either Crohn's disease (CD) or ulcerative colitis (UC), that were followed-up as outpatient in our IBD clinic. To be included, patients had to be in clinical remission. All patients signed the informed consent, and filled a written questionnaire to categorise the importance they assigned to symptoms of the disease and also completed the IBDQ-9 questionnaire to measure QoL. Results: Two-hundred and twenty-five patients were included in the study, 116 with an UC diagnosis and 109 with CD. The most commonly prescribed treatments were salicylates in UC patients (44.9%), thiopurines and antiTNFα agents in CD patients (41.5 and 42.5%, respectively). The four symptoms patients considered most important were abdominal pain (20%), fatigue (17%), rectal bleeding (16%) and diarrhoea (15%). Although abdominal pain and rectal bleeding were the most frequently categorised important symptoms (CD and UC patients respectively), fatigue was the only categorised symptom that was associated with a significantly lower IBDQ-9 score (median score of 63 vs. 72, p < 0.01). Multiple regression analysis identified fatigue and female gender as the independent variables associated with lower IBDQ-9 scores ( p < 0.01). Conclusions: Self-categorising fatigue as an important symptom by IBD patients is associated with a poorer quality of life.